Macroeconomic disasters and forward-looking consumers: historical evidence and evidence from the Covid-19 pandemic - Lorenzo Pozzi; Barbara Sadaba (Tinbergen Institute, 2021)
Macroeconomic disasters (wars, pandemics, depressions) are characterized by drastic shifts and increased volatility of the aggregate consumption to income ratio. By standard intertemporal budget constraint logic, this ratio is linked to expectations of future income and consumption growth rates. We investigate whether these expectations suffice to explain the shifts in the consumption-income ratio that occur during disaster periods or whether, on the other hand, consumers become more forward-looking and therefore give more weight to these expectations during disaster times. Our theoretical framework implies that the predictive ability of the current consumption-income ratio for future income and consumption growth rates is higher during disaster episodes. We check this both for past disasters and the current Covid-19 pandemic through the estimation of panel data regressions for industrial economies using historical annual data (1870 - 2015) and recent quarterly data (1995Q1 - 2020Q4). Our estimations confirm that macroeconomic disasters, contrary to ordinary recessions, make consumers more forward-looking.
Keywords: C23; E21; 330; consumption; saving; macroeconomic disasters; Covid-19; panel data